Die jungpleistozäne Vergletscherung im Vorland der Apolobamba-Kordillere (Bolivien) - Lauer, Wilhelm; Rafiqpoor, M. Daud (ERDKUNDE, 1986)
The paper deals with the Late Pleistocene glaciation of the Cordillera de Apolobamba. Maps and profiles, which have been made by field studies and from aerial photographs, are interpreted. Obviously, three marked advances of glaciers occured during the Late Pleistocene. According to morphological observations, the first of these advances belongs to the maximum Late Pleistocene period (Canlaya Phase), whereas the following advances took place in the late glacial period (Chacabaya-Phases A and B). By analogy with the investigations of Servant and Fontes (1978) the Canlaya-Phase, parallel to the glacial high level of Lake Minchin, is timed between 35 000 and 28 00 B.P., the Chacabaya-Phases,parallel to the high level of Lake Tauca, between 14 000 and 10 000 B.P. The results are compared with those of other authors (see Tab. 1). The post-glacial advances of glaciers are rather unimportant. Pollen-analysis and 14C-dating testify the relatively small climatic fluctuations during the Holocene.